Efficient generation of transgenic reporter strains and analysis of expression patterns in Caenorhabditis elegans using library MosSCI. Issue 9 (25th July 2016) - Kaymak, Ebru; Farley, Brian M.; Hay, Samantha A.; Li, Chihua; Ho, Samantha; Hartman, Daniel J.; Ryder, Sean P.
Abstract : Background : In C. elegans, germline development and early embryogenesis rely on posttranscriptional regulation of maternally transcribed mRNAs. In many cases, the 3′ untranslated region (UTR) is sufficient to govern the expression patterns of these transcripts. Several RNA‐binding proteins are required to regulate maternal mRNAs through the 3′UTR. Despite intensive efforts to map RNA‐binding protein–mRNA interactions in vivo, the biological impact of most binding events remains unknown. Reporter studies using single copy integrated transgenes are essential to evaluate the functional consequences of interactions between RNA‐binding proteins and their associated mRNAs.Results : In this report, we present an efficient method of generating reporter strains with improved throughput by using a library variant of MosSCI transgenesis. Furthermore, using RNA interference, we identify the suite of RNA‐binding proteins that control the expression pattern of five different maternal mRNAs.Conclusions : The results provide a generalizable and efficient strategy to assess the functional relevance of protein–RNA interactions in vivo, and reveal new regulatory connections between key RNA‐binding proteins and their maternal mRNA targets. Developmental Dynamics 245:925–936, 2016 . © 2016 Wiley Periodicals, Inc.